Temporal changes in soil microbial properties and nutrient dynamics under climate smart agriculture practices - Jat, Hanuman Sahay; Choudhary, Madhu; Datta, Ashim; Yadav, Arvind Kumar; Meena, Murli D; Devi, Ritu; Gathala, Mahesh Kumar; Jat, Mangi Lal; McDonald, Andrew J.; Sharma, Parbodh Chander (Elsevier, 2020)
Climate smart agriculture (CSA) practices are emerging as sustainable alternative to conventional rice-wheat system to pull up natural resources degradation across south Asia. After five years of continuous CSA based experiment, a two years study was conducted to evaluate changes in microbial biomasses (microbial biomass carbon and nitrogen), enzyme activities (alkaline phosphatase, dehydrogenase and β-glucosidase), nutrient release and uptake (N, P and K) at different wheat crop growth stages. Effect of CSA practices was also studied for carbon mineralization in an incubation experiment. Four scenarios (Sc) were included in this study- conventional tillage (CT) based rice-wheat system (Sc1), partial CSA based rice-wheat-mungbean system (Sc2), full CSA based rice-wheat-mungbean system (Sc3), and full CSA based maize-wheat-mungbean system (Sc4). Soil samples were collected from scenarios at 0–15 and 15−30 cm depth at different growth stages of wheat crop namely sowing, crown root initiation (CRI), active tillering, panicle initiation, and harvesting. Analysis of soil was done for chemical properties viz. pH, electrical conductivity, available N, P, K, NPK uptake and mineralizable carbon and biological properties viz., microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), dehydrogenase activity (DHA), alkaline phosphatase activity (APA) and β-glucosidase. Significantly higher microbial biomass carbon (42 %) and nitrogen (79 %) were found in surface soil (0−15 cm depth) under CSA based scenarios (Sc2, Sc3 and Sc4) at harvest stage of wheat over CT based/ conventional scenario (Sc1). At surface soil, alkaline phosphatase, dehydrogenase and β-glucosidase activity was 58, 14 and 13 % higher in CSA based scenarios, respectively than CT based scenario. CSA based scenarios showed significantly higher C mineralization after 3 days of the incubation experiment at harvest. An increase of respectively 15, 48 and 17 % of N, P and K uptake was observed with CSA based scenarios than CT based scenario. At harvest stage, 7 % higher amount of dry matter was reported with full CSA based scenarios (mean of Sc2 to Sc4) compared to Sc1. Higher wheat grain yield of ∼10 % was recorded with CSA based scenarios over CT based scenario. Therefore, CSA based scenarios with improved biological properties and nutrient availability and uptake at different wheat growth stages resulted in higher yields and hence need to be popularized among the farmers.